Concurrent Validity and Reliability of Footwork Ability Test Based on The Internet of Things Technology for Badminton Player - Williyanto, Septian; Andre Yogaswara; Witri Suwanto; Agus Wiyanto; Sri Wicahyani; Oktoviana Nur Ajid; Muchamad Rizki Sentani (Universitas Negeri Semarang, 2024)
The purpose of this study is to evaluate the device of footwork ability test based on the Internet of Things technology for badminton players, an online tool for testing badminton players’ agility, for validity and reliability. The data collection method used is by testing two devices on samples. A side step test, an agility test kit, and a footwork ability test were used to evaluate several badminton players. Members of the student activity unit at Universitas Pendidikan Indonesia who play badminton make up the research sample. Each sample carried out the test 2 times, the first test with a side step test (Edgren) and the second test with a footwork device test. The footwork ability test is a valid and reliable way to gauge a badminton player’s agility. Based on the test results of the two test tools (footwork ability test based on the Internet of things and side step test) conducted on 12 players, the validity level of the footwork ability test based on the Internet of things is 0.93 and a reliability of 0.98. So it can be concluded that the device of footwork ability test based on the Internet of Things technology for badminton players’ validity and reliability falls into the good category, making it recommended as a footwork agility test tool for badminton players.